Conflict Resolution in Post-Conflict Maluku: Integrating Lewis Coser's Safety Valve Theory and Pope Francis' Theology of Reconciliation - Cayetanus Andreas Masriat; Artemio P. Millo Jr. (Peradaban Journal of Religion and Society, 2026)
Sustainable conflict resolution in multicultural societies requires not only effective mechanisms for managing social tensions but also moral transformation capable of restoring fractured relationships. Although sociological and theological approaches to reconciliation have been widely discussed, their integration remains underexplored, particularly in the context of post-conflict Maluku. This study analyzes the relationship between Lewis Coser's safety valve theory and Pope Francis' theology of reconciliation and examines their relevance for conflict resolution in post-conflict Maluku. This study employs a qualitative library research design with a conceptual analysis approach. Primary sources include Lewis Coser's writings on conflict theory and Pope Francis' encyclical Fratelli Tutti, supported by scholarly literature on conflict resolution and the Maluku communal conflict. The findings reveal that safety valve mechanisms, including dialogue, customary institutions, and the leadership of religious and traditional authorities, play an important role in preventing the escalation of communal conflict. However, sustainable peace requires more than institutional conflict management. Pope Francis' emphasis on love, forgiveness, justice, and fraternity complements Coser's sociological perspective by providing the moral foundations necessary for enduring reconciliation. This study proposes an integrative socio-religious framework that combines structural conflict management with moral reconciliation, offering a conceptual contribution to conflict resolution and peacebuilding in multicultural societies. Resolusi konflik yang berkelanjutan dalam masyarakat multikultural tidak hanya memerlukan mekanisme yang efektif untuk mengelola ketegangan sosial, tetapi juga transformasi moral yang mampu memulihkan hubungan antarmanusia yang retak. Meskipun pendekatan sosiologis dan teologis terhadap rekonsiliasi telah banyak dikaji, integrasi keduanya masih jarang dibahas, khususnya dalam konteks Maluku pascakonflik. Penelitian ini bertujuan menganalisis hubungan antara teori safety valve Lewis Coser dan teologi rekonsiliasi Paus Fransiskus serta mengkaji relevansinya bagi resolusi konflik di Maluku pascakonflik. Penelitian ini menggunakan desain penelitian kepustakaan kualitatif dengan pendekatan analisis konseptual. Sumber utama penelitian meliputi karya-karya Lewis Coser tentang teori konflik dan ensiklik Fratelli Tutti karya Paus Fransiskus, yang didukung oleh berbagai publikasi ilmiah mengenai resolusi konflik dan konflik komunal di Maluku. Hasil penelitian menunjukkan bahwa mekanisme safety valve, seperti dialog, lembaga adat, serta kepemimpinan tokoh agama dan tokoh adat, berperan penting dalam mencegah eskalasi konflik komunal. Namun, perdamaian yang berkelanjutan tidak dapat dicapai hanya melalui pengelolaan konflik secara institusional. Penekanan Paus Fransiskus pada kasih, pengampunan, keadilan, dan persaudaraan melengkapi perspektif sosiologis Lewis Coser dengan menyediakan landasan moral bagi rekonsiliasi yang berkelanjutan. Penelitian ini menawarkan suatu kerangka konseptual sosio-religius yang mengintegrasikan pengelolaan konflik secara struktural dengan rekonsiliasi moral sebagai kontribusi konseptual bagi kajian resolusi konflik dan pembangunan perdamaian dalam masyarakat multikultural.